Influence of piperine on ibuprofen inducedantinociception and its pharmacokinetics - Venkatesh, Sama; Durga, Kowuru Devi; Padmavathi, Yenumula; Reddy, Bommineni Madhava; Mullangi, Ramesh (Arzneimittelforschung, 2011)
Piperine (CAS 94-62-2), an alkaloid obtained from Piper nigrum and P. longum, is a known inhibitor of various enzymes (CYP isozymes) responsible for biotrans- formation of drugs. By inhibiting the metabolism of drugs, piperine improves the bioavailability of drugs. In the present study piperine (10 mg/kg) significantly increased the dose-dependent antinociceptive activity of ibuprofen evaluated by both acetic acid writhing and formalin test, when it was administered with ibuprofen. Ibuprofen plasma concentration was also increased when it was administered with piperine. The synergistic antinociception activity of ibuprofen when administered with piperine can be attributed to increased plasma concentration of ibuprofen. From this study it can be concluded that piperine can be used as a bioenhancer along with ibuprofen.
Keywords: Bioenhancer; Ibuprofen; Piperine; Synergistic antinociception